(untitled) (Research, Society and Development, 2021)
Hysterectomy is the act of surgical removal of the uterus, performed by vaginal, abdominal and laparoscopic abdominal routes. The decision to use the uterus removal route is suggestive of several predisposing factors, including cervical cancer. The present study aims to analyze the indications for hysterectomy in patients affected by cervical cancer. This is an integrative literature review published between 2015 and 2021, performed in the Medical Literature Analysis Retrievel System Online (MEDLINE), Scientific Electronic Library Online (SCIELO) and Latin American and Caribbean Health Sciences databases (LILACS). The results showed that hysterectomy is the method of choice when the cervical is advanced or when other treatment methods have not had the expected success. There is still controversy in the literature regarding the exact time to perform the procedure, considering that some authors support the idea that the procedure should be performed in the early stages of the disease. Despite the controversies, hysterectomy has been the procedure adopted for the treatment of cervical cancer, and has shown satisfactory results regarding the staging of the neoplasm. However, health professionals need to assess the possible repercussions on women after organ loss and offer the adequate support for them.